Mileage-Based User Fees for Transportation Funding A Primer for State and Local Decisionmakers - Sorensen, Paul (RAND Corporation, 2012)
This primer presents some promising and innovative mileage fee system designs and transition strategies. For states or localities that are considering a transition to mileage fees, awareness of these strategies can help determine whether shifting from fuel taxes to mileage fees merits further consideration. For jurisdictions already engaged in detailed assessments of mileage fees, these concepts can help reduce costs and build public support.